Effect of density on physicochemical and thermal conversion characteristic of Naomaohu coal. (15th January 2021) - Chen, Tianju; Dai, Ruowei; Yellezuome, Dominic; Zhang, Ke; Zhao, Ruidong; Liu, Guangrui; Wu, Jinhu
Abstract: Three coal samples with different density (d < 1.35, 1.35 < d < 1.40 and d > 1.40 g cm −3 ) which were separated using ZnCl2 specific gravity liquid from Naomaohu (NMH) coal were investigated to understand the difference in their physicochemical and thermal properties. Fourier transform infrared spectrometry (FTIR), Raman, X-ray diffraction (XRD), solid-state 13 C Nuclear Magnetic Resonance ( 13 C NMR) and scanning electron microscopy (SEM) methods were used to determine the physicochemical characteristics of the coal sample. In addition, a TG-FTIR analyzer was used to investigate the key thermal conversion characteristics and volatile emissions of the three coal samples. Typical volatile contents including CO2, CO, CH4, and Aromatic CC were analyzed. Results showed that the density has great effect on functional groups and crystalline structure on coal sample. Four distinct peaks are showed in DTG curves, indicating that four reaction stages, namely, drying, desorption, pyrolysis, and polycondensation, were involved in the pyrolysis process of NMH coal. The TG/DTG curves of the three densities indicate that the low-density coal assumes the highest weight loss rate at the pyrolysis stage and the trend becomes weaker at the polycondensation stage. Two obvious emission peaks vividly showed that light gases such as CO2, CO, and CH4 can be separated into two stages at the pyrolysis and polycondensation stage.